Local Legislation on Qur'anic Education in Gorontalo Province Were Crafted Using a Hybrid of Islamic Law and Positive Law - Gobel, Rahmat Teguh Santoso; Husnan, Moh. Ihsan; Nggilu, Novendri; Adnan, Raihan Sahrul; Muhtar, Mohamad Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Issues with regional rules on Koranic education in Gorontalo Province are discussed. This is because the draft regional law on Koranic education is merged with preexisting regional regulations for the provision of education, as stated by the Ministry of Home Affairs. As a methodology, normative legal study will provide solutions to these issues. The author employs this legal research method because it allows for a comprehensive assessment of relevant literature, statutes, and judicial decisions. This article draws the conclusion, supported by the study's findings, that a regional regulation on Qur'anic education in the province of Gorontalo may contradict with the principles of forming legislation. This is because the establishment of regional regulations should never lead to discrimination of any kind, and this is based on the content of regional regulations that mandate protection for all groups and religions. A legal policy for the Gorontalo Provincial government is required to accommodate Qur'anic education in regional regulations regarding the implementation of education in the region so that, in the long run, the values of the Koran are not only accepted in the sociol Later, the values of the Koran are not only accepted in the sociol. Therefore, it is essential to update regional regulations on the implementation of education to include a chapter on religious education that regulates not just Koranic education but also education in other religions. As a follow-up to the revision of regional regulations on the implementation of education, the governor's regulation on Koranic education is required.